Literature Analysis on the Effectiveness of the Realistic Mathematics Education (RME) Approach in Improving Students' Understanding of Mathematical Concepts - Lalu Aji Muliardi Akbar; Alvandi Nova (Gema Cendekia Institute, 2025)
This study aims to analyze the effectiveness of the Realistic Mathematics Education (RME) approach in improving students' understanding of mathematical concepts through the synthesis of the latest research results. The main problem behind this study is the low ability of students to understand mathematical concepts, which is shown through difficulties in connecting ideas, explaining mathematical reasons, and applying concepts in new contexts. This study uses the Systematic Literature Review (SLR) approach by examining articles from the Scopus, ScienceDirect, Taylor & Francis, and SpringerLink databases, and verified through Google Scholar. The article selection follows the PRISMA flow, with the inclusion criteria for articles published in 2020–2025, peer-reviewed status, applying RME in learning, and measuring concept understanding. A total of 5 articles were selected and analyzed through thematic synthesis to identify implementation patterns, outcomes, as well as supporting and inhibiting factors for the implementation of RME. The results show that RME consistently effectively improves understanding of mathematical concepts through the use of real contexts, step-by-step modeling, and reflective discussions that encourage the construction of meaning. However, the success of the implementation is greatly influenced by the readiness of teachers and the quality of learning tools. Thus, this study confirms that RME is a relevant approach and needs to be optimized in mathematics learning through teacher training and the provision of supportive learning media.